Performance Evaluation of Domestic Wastewater Treatment Plant Systems: A Case Study of Domestic Wastewater Systems in Lembah Hijau Housing, Banda Aceh City, Indonesia - Muhammad Syah Iwan; Suhendrayatna Suhendrayatna; Zaki Muhammad (E3S Web of Conferences, 2024)
One of the residential areas in Banda Aceh City that has problems with wastewater management is the Lembah Hijau housing, Lueng Bata District. In 2018, the government has built and operationalized 2 units of Local Domestic Wastewater Management Installation (WWTP) with a service capacity of 50 households per unit and a capacity of 72m3/day. The purpose of this study was to examine the existing conditions and functions of WWTP, technical aspects, social aspects and institutional aspects, and the impact of Communal WWTP on the environment with parameters namely pH, BOD, COD, TSS, oil and grease. The method used in this research is a quantitative method. The results showed that the existing conditions of 2 communal WWTP units in the Lembah Hijau Housing, namely one WWTP unit Jl. Al-Firdaus functions and can be operationalized. One unit of communal WWTP Jl. Barata V could not be operated because the elevation of the house's drain pipe was lower than the installation pipe for the complex shelter being built. The technical aspect is disposal (overflow/ overflow) in which the end of the septic tank is discharged into the local canal or drainage. Test results for pH, BOD, COD, TSS, oils and fats show a BOD value of 54.7 mg/L with a quality standard of 30 mg/L, meaning that the BOD value has exceeded the quality standard. Therefore, the follow-up and management of the wastewater is required. The pH test results were still below the quality standard of 5.5. The COD test result was 92.6 mg/L. Test results against Total suspended Solid (TSS) of 20.9 mg/L with a quality standard of 30 mg/L means that the TSS value is still below the quality book which is still permissible.